DIGITAL-BASED ASSESSMENT OF EARLY CHILDHOOD PORTFOLIO - Intan Yusmarini; Apriana Anggraini; Mala Komalasari; Ayu Vera Dewi; Erna Widiastuti; Fathkul Jannah Putri Ayuni; Yashinta Sitepu; Rivo Panji Yudha (Universitas Panca Sakti Bekasi, 2023)
This study aims to analyze the effectiveness of implementing digital-based portfolio assessment for Early Childhood Education (PAUD) teachers in Kramatwatu District, Serang Regency in improving the learning and assessment process in the PAUD environment. This study used a pre-experimental design , namely by using a one group pretest-posttest type design involving 100 PAUD teachers in Kramatwatu District, Serang Regency. The instrument used in this research uses a questionnaire. The analysis technique performed is using statistical data analysis techniques. This data analysis is used to analyze quantitative data in the form of student learning outcomes which are processed using the T-test through a statistical application, namely SPSS 21 for windows . The steps taken in the use of data processing statistics are (a) normality test; (b) homogeneity test; (c) The T-Test test used is the Paired Sample t test . The results showed that the value of Sig. (2-tailed) is 0.000 <0.05, then H 0 is rejected and H 1 is accepted. So it can be concluded that there is an average difference between the results of the Pre Test and Post Test , which means there is no effect of using digital-based PAUD teacher portfolio assessment.